Fish and Food-Fatale: Food-borne Trematode Opisthorchis viverrini and Cholangiocarcinoma - Tan S.; Machrumnizar M. (Helminthologia, 2023)
Neglected Tropical Diseases (NTDs) are a group of communicable diseases with a long history with human beings. NTDs are the proxy of poverty since they affect those in low-income and extreme-poverty populations, as those populations lack access to proper health care, clean water, sanitary conditions, and hygiene. NTDs create losses for a nation that come from the health and the economic sectors as well since the costs of diagnosis, prevention, and treatment strain the national purse strings. One of the 20 different forms of NTDs on the list is food-borne trematodes, comprises of Fasciola, Paragonimus, Clonorchis, and Opisthorchis. Currently, it is estimated that food-borne trematodes can cause a devastating effect on mortality and morbidity. All of them are zoonotic, as humans become infected by ingestion of a second intermediate host, such as freshwater snails, fish, or water vegetables. Opisthorchis viverrini, one of the food-borne trematodes that can be found mostly in South East Asia regions, especially in the Mekong basin, is regarded as a group 1 carcinogen leading to cholangiocarcinoma (CCA). This study aims to present the updated review of Opisthorchis viverrini and CCA.